Local Development Platforms (LDP): an operational framework for business development - Gast\~ao de Jesus Marques; Cristina Gama Guerra (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose - The purpose of this paper is to present a conceptual model of business development that provides operational ways to increase the competitive presence of more micro and small ventures (both actual and new) in enlarged markets, including international ones. Design/methodology/approach - The paper develops a conceptual model starting from the identification of the most usual constraints limiting the SMEs and entrepreneurship development and success. After this stage, the model was built with the help of selected concepts, which represent a theoretical framework of support. Findings - Regarding the universe of SME and entrepreneurship, the authors usually find some weaknesses: markets mainly local/regional, absence of growth, cooperative networks and/or international operations, because of several usual constraints: limited competences and resources, absence of critical mass on buying/ selling and difficulty to cooperate. These shortcomings represent an economic waste when there are competitive offers and/or endogenous resources. Research limitations/implications - The model will be applied in a Portuguese county, in this way the authors expect to make an empirical research in the near future. Practical implications - The model surpasses the, usual, limited skills of people and organisations betting in their competitive specialisation, with the assumptions that few people can be successful entrepreneurs/ managers, but quite everyone can perform something competitively. The organisation/structure - Local Development Platform (LDP) - has the responsibility to assure the competitiveness of value chains built over networks of these agents. Additionally, the LDP should provide collective resources to lower the investments and operational needs of the agents involved, provide the added value services necessary for offers and agents' competitiveness, achieve critical mass on buying and selling and enlarge/open new markets. These resources are organised in up to five specialised platforms, to service a strategy structured along five axes of development. Social implications - With this model, it is possible to increase the levels of employment and welfare. Originality/value - A practical/operational integrated model able to be applied in different contexts will help private and public agents to define and implement strategies of development to enable the growth and success of SMEs and entrepreneurial initiatives in the international markets context.
Keywords: M00; M01; M19; 650; Business development; Strategy; Networks; Resources; Value chains